Visual interactive Islamic learning system for children - Abu Bakar, Nur Fadhilah; Ashrafia, Shahnaz; Zeki, Akram M.; Abubakar, Adamu (Design for Scientific Renaissance, 2013)
Research shows that approximately 65% of the population is visual learners because the brain processes visual information 60,000 faster than text. Moreover 90% of information that comes to the brain is visual and 40% of all nerve fibers connected to the brain are linked to the retina. Thus visual aids in the classroom improve learning by up to 400 percent. Contrary to the common way of teaching in schools nowadays that involves using text books, verbal explanation and writings at whiteboard for both western and Islamic teaching. This paper presents an approach that will be utilize in order to capture children attention towards understanding Islamic teaching easily and to give teachers more flexibilities in teaching Islam. Thus, an interactive web base system is designed to offers basic knowledge of Islamic concepts that include: Iqra’, daily duahs, steps in performing both ablution and salah, 3D presentation of the stories of the prophet, Islamic songs, Islamic videos and games.